Hubungan Pemakaian Kb Suntik Dengan Kenaikan Berat Badan Dan Gangguan Menstruasi Di Tpmb Siluh Made Sukawati Kota Tangerang Selatan Tahun 2024 - Ria Susanti; Susaldi; Madinah Munawaroh Hayatullah (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
The use of 3-monthly injectable contraception has a major side effect, namely changes in body weight. Weight gain is a risk factor for various diseases, including heart, kidney, nerve disorders, and blood vessel disorders. The purpose of this study was to determine whether there was a relationship between the use of contraceptive injections and weight gain and menstrual disorders in KB acceptors at TPMB Siluh Made Sukawati, South Tangerang City in 2024. The method used in this study was an analytical survey, namely a survey or research that tries to explore how and why this phenomenon occurs. With a cross-sectional approach.The results showed that respondents who experienced weight gain> 2.3 kg with the use of contraceptive injections> 2 years were 34 respondents (56.7%). The results of the statistical test obtained a value of p = 0.000 (p <0.05) so H0 was rejected and the results showed that respondents who experienced menstrual disorders with the use of contraceptive injections <2 years were 40 respondents (66.7%). The results of the statistical test obtained a value of p = 0.000 (p <0.05) so H0 was rejected. Conclusion There is a significant relationship between weight gain and the use of 3-month contraceptive injections with a duration of use of more than 2 years. And there is a significant relationship between menstrual disorders and the use of 3-month injection contraception with a duration of use of more than 2 years.